Development of Coconut Trunk Fiber Geopolymer Hybrid Composite for Structural Engineering Materials. (March 2017) - Amalia, F; Akifah, N; Nurfadilla,; Subaer,
Abstract: A research on the influence of coconut fiber trunk on mechanical properties based on fly ash has been conducted. The aims of this study was to examine the mechanical properties of geopolymer composites by varrying the concentration of coconut trunk fiber. Geopolymer synthesized by alkali activated (NaOH+H2O+Na2O.3SiO2) and cured at the temperature 700C for one hour. Specimens were synthesized into 5 different mass of fiber 0 g, 0.25 g, 0.50 g, 0.75 g, and 1.00 g keeping fly ash constant. The highest compressive strength was 89.44 MPa for specimen added with 0.50 g of fiber. The highest flexural strength was 7.64 MPa for the same sample. The interfacial transition zone (ITZ) between the matrix of geopolymers and coconut fiber was conducted by using Scanning Electron Microscopy-Energy Dispersive Spectroscopy (SEM-EDS). The chemical composition of the specimen was examined by using X-Ray Diffraction (XRD). The thermal properties of coconut fiber trunk was analyzed using Differential Scanning Calorimetry (DSC). It was found that coconut fiber was able to improve the mechanical and microstructure properties of geopolymers composites.